Pericyte recruitment in human corneal angiogenesis: an ultrastructural study with clinicopathological correlation. Issue 1 (1st January 2003) - Cursiefen, C; Hofmann-Rummelt, C; Küchle, M; Schlötzer-Schrehardt, U
Abstract : Background/aim: During angiogenesis—that is, the outgrowth of new from pre-existing blood vessels, new capillaries undergo a period of "fine tuning" when vascular endothelial cells become apoptotic if sufficient supply of angiogenic factors is lacking. Morphologically, this period correlates with the absence of pericyte coverage of new vessels. Mature, pericyte covered vessels, in contrast, do not depend on elevated levels of angiogenic factors for survival. This study analyses whether, and if so when, pathological vessels in human corneal neovascularisation (CN) acquire pericyte coverage. This can be of importance for future angioregressive therapeutic strategies. Methods: Vascularised human corneas obtained by keratoplasty were evaluated by electron microscopy for pericyte coverage of new vessels. These data were correlated with the duration of CN (mean 73 (SD 95) (range 0.5–360) months; n = 15). CN was secondary to keratitis, transplant rejection, aniridia, or trauma. Results: Overall, 196 blood vessels were analysed ultrastructurally (72 (37%) capillaries, 122 (62%) venules, and two (1%) arterioles). Electron microscopically, 170 (87%) vessels were covered by pericytes and two (1%) in addition by smooth muscle cells. Pericyte recruitment increased with time, evolving between clinically noted onset of CN and keratoplasty. Already 2 weeks after onset of CN, more than 80% of new vessels were covered by pericytes. Conclusion: Pathological new vessels in human corneal angiogenesis are rapidly covered by pericytes. Therapeutic strategies aimed at regression of immature, not yet pericyte covered vessels by antagonising angiogenic factors should thus be most effective if applied very early in the course of corneal neovascularisation.